Answer: (y - 2) (y -3)
Step-by-step explanation:
Answer:
x = 3 + √6 ; x = 3 - √6 ;
; 
Step-by-step explanation:
Relation given in the question:
(x² − 6x +3)(2x² − 4x − 7) = 0
Now,
for the above relation to be true the following condition must be followed:
Either (x² − 6x +3) = 0 ............(1)
or
(2x² − 4x − 7) = 0 ..........(2)
now considering the equation (1)
(x² − 6x +3) = 0
the roots can be found out as:

for the equation ax² + bx + c = 0
thus,
the roots are

or

or
and, x = 
or
and, x = 
or
x = 3 + √6 and x = 3 - √6
similarly for (2x² − 4x − 7) = 0.
we have
the roots are

or

or
and, x = 
or
and, x = 
or
and, x = 
or
and, 
Hence, the possible roots are
x = 3 + √6 ; x = 3 - √6 ;
; 
Answer:
x=35
Step-by-step explanation:
180-147=33 (angles in a straight line)
33+3x+42=180 (angles in a triangle)
3x+42=147
147-42=105
105/3=35
Answer:
5
Step-by-step explanation:
Let's call the length AD y.

Hope this helps!
Answer:
we use distributive property.
Step-by-step explanation:
for example:
4(5x+7)=
4x5x=20x
4x7=28
so the answer is:
20x+28
hope this helps : )